2010
DOI: 10.1111/j.1365-2427.2008.02124.x
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous inference of zooplanktivorous fish and macrophyte density from sub‐fossil cladoceran assemblages: a multivariate regression tree approach

Abstract: 1. Quantitative palaeolimnology has traditionally sought to quantify species-environment relationships to use alterations in biological assemblages to reflect past environmental change. Transfer functions have used regression techniques, such as weighted averaging, to define taxon optima and tolerance for a single chemical or biological variable. 2. Cladoceran assemblages and their sub-fossil remains in shallow lakes are shaped by a combination of interacting factors. Partial constrained ordination of sub-foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 71 publications
(93 reference statements)
0
85
0
Order By: Relevance
“…2), its littoral affinities in the lake may have been driven by these food-rich vegetative habitats because it is shown to aggregate at food-rich habitats among macrophytes (Cerbin et al, 2003). However, since top-down control of fish on cladoceran zooplankton is well established and also more important in shallow sites (Jeppesen et al, 1997(Jeppesen et al, , 2003, and the coupling effects of fish and aquatic macrophytes in structuring cladoceran communities are well known (Jeppesen et al, 1997;Davidson et al, 2007Davidson et al, , 2010a, fish predation and presence of macrophytes most likely had high influence in structuring the intra-lake distribution of cladoceran zooplankton in Lake PieniKauro. In addition to horizontal migration from pelagial into littoral macrophyte stands occurring as a means to avoid fish predation (Burks et al, 2002), 'shore avoidance' behavior of large-bodied zooplankton acts as an efficient mechanism to avoid high predation risk in near-shore habitats (Gliwicz & Rykowska, 1992).…”
Section: Influence Of Water Depth On Intra-lake Cladocera Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation
“…2), its littoral affinities in the lake may have been driven by these food-rich vegetative habitats because it is shown to aggregate at food-rich habitats among macrophytes (Cerbin et al, 2003). However, since top-down control of fish on cladoceran zooplankton is well established and also more important in shallow sites (Jeppesen et al, 1997(Jeppesen et al, , 2003, and the coupling effects of fish and aquatic macrophytes in structuring cladoceran communities are well known (Jeppesen et al, 1997;Davidson et al, 2007Davidson et al, , 2010a, fish predation and presence of macrophytes most likely had high influence in structuring the intra-lake distribution of cladoceran zooplankton in Lake PieniKauro. In addition to horizontal migration from pelagial into littoral macrophyte stands occurring as a means to avoid fish predation (Burks et al, 2002), 'shore avoidance' behavior of large-bodied zooplankton acts as an efficient mechanism to avoid high predation risk in near-shore habitats (Gliwicz & Rykowska, 1992).…”
Section: Influence Of Water Depth On Intra-lake Cladocera Assemblagesmentioning
confidence: 99%
“…In addition, cladocerans are not a homogenous group in respect to their habitats, feeding, or positions in the foodwebs, and several other chemical and physical Table 2 Distribution of most abundant body parts (C = carapace, H = headshield, P = postabdomen, E = ephippium) of the common chydorid species (shown in Fig. 2) encountered in Lake Pieni-Kauro and River Saavanjoki along the water depth gradient from the shallowest (1) (Korhola, 1999;Jeppesen et al, 2001;Amsinck et al, 2005;Sweetman & Smol, 2006;DeSellas et al, 2008;Davidson et al, 2010a). The ordinations specified some habitat affinities (Figs.…”
Section: Influence Of Water Depth On Intra-lake Cladocera Assemblagesmentioning
confidence: 99%
“…Recent studies have presented innovative ways of addressing the fact that multiple rather than single structuring forces tend to influence changes in lake communities. Davidson et al (2010a) showed that both submerged macrophyte abundance and zooplanktivorous fish influence cladoceran communities in shallow lakes of the UK and Denmark, and they developed a multivariate regression tree model that incorporated both explanatory variables. They observed six break points at which fish density and macrophyte abundance influenced significant changes in sub-fossil cladoceran assemblages.…”
Section: Limitations Of Univariate Transfer Functions and New Approamentioning
confidence: 99%
“…Size-selective predation on larger cladoceran species could increase the relative abundance of some planktonic species. For example, the rise of Bosmina longirostris in concert with the density of zooplanktivorous fish could also result in an absence of Daphnia pulex (Davidson et al 2010). However, changes associated with size-selective predation of larger species (e.g., Daphnia spp.)…”
Section: Reliability Of the Cladoceran-based Temperature Reconstructionmentioning
confidence: 99%
“…sphaericus; a slight increase in zooplanktivorous fish density may have resulted in the absence of these taxa. These cladocerans are abundant in temperate lakes and mires and are strongly associated with the presence of aquatic macrophytes at lower fish densities (Davidson et al 2010). However, their T July optima are similar to those of small-bodied Bosminidae, ca.…”
Section: Reliability Of the Cladoceran-based Temperature Reconstructionmentioning
confidence: 99%